Pelatihan Relaksasi Bumil Sehat untuk Menurunkan Kecemasan Ibu Hamil Risiko Tinggi - Libbie Annatagia; Sofia Retnowati (JIP (Jurnal Intervensi Psikologi), 2011)
A growing body of research indicates that maternal anxiety is a significant risk factor for adverse pregnancy and birth outcome. This study evaluated the effectiveness of "Relaksasi Bumil Sehat" training for high-risk pregnant women's anxiety. 8 women were assigned into 2 groups: experiment and control group. Treatment was administered in small group that met for 5 sessions. Pregnancy Anxiety Scale were completed before and after treatment. Result showed that "Relaksasi Bumil Sehat" was significantly effective to reduced high-risk pregnant women's anxiety (p=0,029). These data support the central role of "Relakasi Bumil Sehat" training in the understanding and treatment of high-risk pregnant women's anxiety.Keywords: Relaksasi bumil sehat, anxiety high-risk pregnant women